Using health impact assessments to implement the sustainable development goals in practice: a case study in Wales. Issue 3 (3rd May 2020) - Green, Liz; Gray, Benjamin J; Ashton, Kathryn
ABSTRACT: Welsh Government's (WG) Wellbeing of Future Generations (Wales) Act 2015 (Welsh Government 2015) is a unique legislation which demonstrates its commitment to sustainable development. It is the only global legislation that enshrines the UNs Sustainable Development Goals (SDGs) within it. It emphasises WGs commitment to a 'Health in All Policies' approach to policymaking by emphasising the sustainable development principle is integrated to address seven Wellbeing Goals. Two of these goals are focussed on health and (in)equality which ties them distinctly to the practice of Health Impact Assessment (HIA). The World Health Organisation recommends the use of HIA to achieve the SDGs but not how to practically do this. This paper describes a HIA undertaken on a proposed major electricity cable connection development in Wales. It discusses how this HIA was the catalyst for considered thinking about the HIA process and how it can be used to consider and implement the Well-being Goals in practice, and initiates further thinking about how this can be extended to implement and address the SDGs at a local, regional and national level.